1993
DOI: 10.1515/zna-1993-1-206
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Diffraction Study of the Electron Density and Anharmonicity in K2PtCl6

Abstract: X-ray diffraction data in heavy-atom compounds may be sensitive to anharmonic atomic displacements, since the large core electron densities result in appreciable scattering amplitudes at large reciprocal distances. Since bonding electron densities may also exhibit sharp features affecting high-order reflections, they may be difficult to distinguish from anharmonic effects. We have analyzed an accurate room-temperature single-crystal X-ray data set of K 2 PtCl 6 using least-squares anharmonic displacement and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…In both cases electron depletion along the K-Pd vector is stronger than that along a vector at right angles. The features around the K atom for the isomorphic K2PtCl6 compound in corresponding Ap maps obtained by Restori & Schwarzenbach (1993) closely resemble those around K in K2SiF6, shown in Fig 4. The heights of the difference-density peaks for the K2PdCI6 and K2SiF6 structures differ, perhaps because the approach to extinction correction differs in the two studies. When a least-squares extinction correction similar to that used by Restori & Schwarzenbach (1993) is applied to the K2PdCI6 data of Hester et al (1993a), positive features similar to those observed for the other compounds appear.…”
Section: K-atom Densitiessupporting
confidence: 55%
See 2 more Smart Citations
“…In both cases electron depletion along the K-Pd vector is stronger than that along a vector at right angles. The features around the K atom for the isomorphic K2PtCl6 compound in corresponding Ap maps obtained by Restori & Schwarzenbach (1993) closely resemble those around K in K2SiF6, shown in Fig 4. The heights of the difference-density peaks for the K2PdCI6 and K2SiF6 structures differ, perhaps because the approach to extinction correction differs in the two studies. When a least-squares extinction correction similar to that used by Restori & Schwarzenbach (1993) is applied to the K2PdCI6 data of Hester et al (1993a), positive features similar to those observed for the other compounds appear.…”
Section: K-atom Densitiessupporting
confidence: 55%
“…The features around the K atom for the isomorphic K2PtCl6 compound in corresponding Ap maps obtained by Restori & Schwarzenbach (1993) closely resemble those around K in K2SiF6, shown in Fig 4. The heights of the difference-density peaks for the K2PdCI6 and K2SiF6 structures differ, perhaps because the approach to extinction correction differs in the two studies. When a least-squares extinction correction similar to that used by Restori & Schwarzenbach (1993) is applied to the K2PdCI6 data of Hester et al (1993a), positive features similar to those observed for the other compounds appear. A change in the scale factor affects the strong low-angle reflections significantly, but in so far as the local topography is derived from the bulk of the reflections which, being weaker, are affected less strongly by the scale factor, the topographies correspond closely.…”
Section: K-atom Densitiessupporting
confidence: 55%
See 1 more Smart Citation
“…Model (i) provided the most economical parametrization but this is per se not sufficient to prove the presence of anharmonic motions. The corresponding difference electron-density maps (Restori & Schwarzenbach, 1993, 1995 show a prominent octopolar density centered on K with maxima of "-'0.5 e ~-3 peaking on the tetrahedral (111) directions at ~0.4.~. from the atom center.…”
Section: Electron Density Of K2ptclmentioning
confidence: 99%
“…However, anharmonic motions of the metal atom may result in similar features since they are expected to have larger amplitudes in directions towards secondnearest neighbors and smaller amplitudes towards nearest neighbors. The electron density in K2PtC16 (Restori & Schwarzenbach, 1993) presents another example that is at the origin of the present work: it may be parametrized in terms of both anharmonic and multipolar functions since 3p shows compact features close to the atomic centers.…”
Section: Introductionmentioning
confidence: 99%